DIGITALISASI ADMINISTRASI PUSKESMAS MAJASARI PANDEGLANG MELALUI PELATIHAN APLIKASI PERKANTORAN - Irmanda, Helena Nurramdhani; Zaidiah, Ati; Widiastiwi, Yuni; Astriratma, Ria; Isnainiyah, Ika Nurlaili (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2025)
The digitalization of administration in healthcare facilities is a strategic step to enhance service efficiency and accuracy. Puskesmas Majasari continues to face challenges in managing its administrative processes, as data recording and reporting are predominantly performed manually. This condition leads to potential errors in data entry, delays in report generation, and a lack of administrative efficiency. This community service program aims to provide training on the use of office applications to the staff at Puskesmas Majasari to support the digitalization of administrative data management. The implementation method involves three main stages: preparation, training execution, and result evaluation. The training is conducted through hands-on practice and interactive discussions, covering the use of Microsoft Word and Excel for the administrative needs of the health center. The evaluation results indicate an increase in the participants’ average score from 58.33 in the pre-test to 70.60 in the post-test, reflecting an improvement of 12.27 points. Reflective discussions revealed that participants found the training beneficial, though further training is needed to cover advanced features such as pivot tables. It is recommended to conduct additional training and provide more adequate facilities to support sustainable digital transformation. This program is expected to accelerate the digitalization of administration at Puskesmas Majasari and enhance the overall quality of healthcare services.